2021
DOI: 10.1155/2021/8850256
|View full text |Cite
|
Sign up to set email alerts
|

Rational Application of First-Line EGFR-TKIs Combined with Antiangiogenic Inhibitors in Advanced EGFR-Mutant Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Purpose. A meta-analysis of randomized controlled trials (RCTs) was conducted to compare the difference in efficacy and safety between epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) with antiangiogenic inhibitors ( A + T ) and EGFR-TKI monotherapy in patients with treatment-naïve advanced EGFR-mutant non-small-cell lung cancer (NSCLC). Methods. PubMed, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Among these treatments, approximately 80% of other targeted therapies are EGFR–TKI. Preclinical studies have shown that VEGF and EGFR share a common downstream signaling pathway ( 25 28 ), but the clinical trial data of EGFR–TKI combined with bevacizumab are still immature and have many uncertainties ( 29 ). Our study confirmed the benefits of bevacizumab (or bevacizumab biosimilar) combined with EGFR–TKI in ORR and PFS but failed to obtain OS results for all patients because of the short follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Among these treatments, approximately 80% of other targeted therapies are EGFR–TKI. Preclinical studies have shown that VEGF and EGFR share a common downstream signaling pathway ( 25 28 ), but the clinical trial data of EGFR–TKI combined with bevacizumab are still immature and have many uncertainties ( 29 ). Our study confirmed the benefits of bevacizumab (or bevacizumab biosimilar) combined with EGFR–TKI in ORR and PFS but failed to obtain OS results for all patients because of the short follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Another statistically significant result was ORR which was higher with the bevacizumab-erlotinib combination (RR = 0.79; 95% CI, 0.64-0.97, p = 0.03). However, higher ORR has not been replicated in all meta-analysis, probably because of heterogeneity (31,(35)(36)(37)(38)(39)(40) . Our analysis only included clinical trials where the combination of bevacizumab and erlotinib was used to maintain a homogeneous population (I 2 = 0%, p = 0.66).…”
Section: Figurementioning
confidence: 99%
“…To improve PFS, TKIs combined with antiangiogenic agents have been investigated. Several trials have suggested that the addition of antiangiogenic agents to TKIs signi cantly reduces the risk of disease progression [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%